Well spoken : teaching speaking to all students - Palmer, Erik , 1953- (Stenhouse Publishers, 2011)
In this book, Erik Palmer shares the art of teaching speaking in any classroom. Teachers will find thoughtful and engaging strategies for integrating speaking skills throughout the curriculum.--[book cover]